2011
DOI: 10.1039/c1jm11239b
|View full text |Cite
|
Sign up to set email alerts
|

Phase behaviour of liquid-crystalline polymer/fullerene organic photovoltaic blends: thermal stability and miscibility

Abstract: The thermal behaviour of an organic photovoltaic (OPV) binary system comprised of a liquidcrystalline fluorene-based polymer and a fullerene derivative is investigated. We employ variabletemperature ellipsometry complemented by photo-and electroluminescence spectroscopy as well as optical microscopy and scanning force nanoscopy to explore phase transitions of blend thin films. The high glass transition temperature correlates with the good thermal stability of solar cells based on these materials. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
95
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(107 citation statements)
references
References 60 publications
9
95
1
Order By: Relevance
“…Consistent with previous observations, we observe a redshift of E CT with increasing C 60 fraction [10][11][12][13][14] , but find that modelling based on the accompanying change in dielectric constant via the solid-state solvation effect (SSSE) 15 can only explain the data at high (450%) C 60 loading. We find that E CT at low fullerene concentration is higher than expected from the change in dielectric constant and attribute this discrepancy to increased localization of the electron component of the CT state because of a reduction in average C 60 crystallite size below B4 nm.…”
supporting
confidence: 79%
“…Consistent with previous observations, we observe a redshift of E CT with increasing C 60 fraction [10][11][12][13][14] , but find that modelling based on the accompanying change in dielectric constant via the solid-state solvation effect (SSSE) 15 can only explain the data at high (450%) C 60 loading. We find that E CT at low fullerene concentration is higher than expected from the change in dielectric constant and attribute this discrepancy to increased localization of the electron component of the CT state because of a reduction in average C 60 crystallite size below B4 nm.…”
supporting
confidence: 79%
“…It has been shown that miscibility is a parameter controlling the fill factor of OPV devices 34 but also their microstructural stability. 13,35 Such polymer arrangement with monomers co-facial to the small molecule acceptor are also likely to be beneficial for charge transfer and thus, charge generation. Thus, we speculate that the knowledge of such specific interactions can lead to the design and selection of small molecule acceptors to improve morphological robustness.…”
Section: -18mentioning
confidence: 99%
“…poly(3-hexylthiophene):phenyl-C 61 -butyric acid methyl ester (P3HT:PCBM), three phases have been recognized 28 and confirmed by other studies. 15,[28][29][30][31][32][33][34][35][36] These consist of a pure, mostly crystalline P3HT phase (also referred to as "aggregated"), a mixed amorphous P3HT:fullerene phase, and a fullerene-rich phase.…”
Section: Introductionmentioning
confidence: 99%